Corpora for terminology extraction : the differing perspectives and objectives of researchers, teachers and language services providers - Maia, Belinda Mary Harper Sousa (2002)
Using corpora to find correct terminology is an activity that is interpreted rather differently according to the final objectives of those involved. This paper will try to show how the perspectives and objectives of researchers, teachers and language services providers do not always coincide, and how this lack of mutual appreciation and understanding can sometimes cause confusion. We shall first look at the more speculative aspects of current terminology research for the possibilities they offer in the future, even though some of this work is not directly related to translation, and consider the reasons why correct terminology is growing in importance in the lives of both domain specialists and language services providers. We shall then briefly consider both the older prescriptive notions of standardisation and the descriptive approach made feasible by technology and corpora today. Corpora in the broadest sense – from formally constructed and officially approved collections of texts to the disposable, do-it-yourself corpora anyone can now collect off the Internet for information on a specific subject – come as part of the information revolution provided by technology. They provide possibilities for any user of language and knowledge that were unthinkable a few years ago, but there are also problems and drawbacks.